Front St., Dawson, Yukon Territory, June 1898. - Hegg, Eric A., 1867-1948 (1898)
Shows dogteam hauling cart in street, "Louis Pond & Co." and "Monte Carlo Theatre" on right Caption on image: "Front St. scene in Dawson June '99.". Klondike Gold Rush.